Eficácia e segurança do uso inalatório da adrenalina-L na laringite pós-intubação utilizada em associação com a dexametasona - Fernandes, Iracema C. O. [UNESP]; Fernandes, José Carlos [UNESP]; Cordeiro, Andréa [UNESP]; Hsin, Shieh H. [UNESP]; Bousso, Albert [UNESP]; Ejzenberg, Bernardo [UNESP]; Okay, Yassuhiko [UNESP] (FapUNIFESP (SciELO), 2001)
Objective: to assess the efficacy and safety of the use of nebulized L-epinephrine associated with dexamethasone in post-intubation laryngitis. Method: we carried out a prospective, randomized, double-blind, placebo controlled study with two cohorts of patients with postintubation laryngitis graded 3 to 6 by Downes and Raphaely score and during two years. Our population was divided into two groups: A and B; both groups received intravenous dexamethasone and nebulized saline with (group B) and without (group A) L-epinephrine. The efficacy was assessed by Downes and Raphaely's score. The side effects of epinephrine were evaluated according to occurrence of arrhythmia, to increased blood pressure, and to average heart rate of group B in comparison to group A. Results: twenty-two patients were included in group A (average score = 4.8) and 19 in group B (average score = 5.2). During treatment, 3 patients in group A presented a score of 8 and were reintubated. This group also showed higher clinical scores than group B during the first two hours of the protocol; these results were not statistically significant. No side effects were observed due to epinephrine. The gasometric parameters were adequate in both groups, but better in the control group. Conclusions: we did not observe increased efficacy for the treatment of post-intubation laryngitis when nebulized L-epinephrine was used simultaneously with intravenous dexamethasone. Some indicators, however, did present a favorable trend when combined therapy was used and should be submitted to further evaluation.
Efficacy and safety of nebulized L-epinephrine associated with dexametasone in post-intubation laryngitis
Keywords: Dexamethasone; Epinephrine; Intubation; Laryngitis; adrenalin; dexamethasone; placebo; adolescent; adult; blood pressure monitoring; child; clinical trial; controlled clinical trial; controlled study; double blind procedure; drug efficacy; drug safety; female; heart arrhythmia; heart rate; human; intubation; laryngitis; male; randomized controlled trial; scoring system